Hydrogenated Amorphous Silicon Microstructuring for 0th-Order Polarization Elements at 1.0–1.1 <tex Notation="TeX">$μ\hbox{m}$</tex> Wavelength - Thomas Kampfe; Svetlen Tonchev; Guillaume Gomard; Christian Seassal; Olivier Parriaux (IEEE Photonics Journal)
Dedicated photolithographic and reactive ion etching processes applied to the plasma-enhanced chemical vapor deposition (PECVD) hydrogenated amorphous silicon layers of solar cells have been developed in the objective of the low-cost manufacturing of efficient, depth-limited subwavelength gratings transforming a linearly polarized beam into a radially and azimuthally polarized beam in the 1.0–1.1- <tex Notation="TeX">$μ\hbox{m}$ </tex> wavelength range.